Increasing incidence of ADHD among children, adolescents and young adults: COVID-19 pandemic-driven trend in Korea (2012–2023) - Sang Min Park; Sun Jae Park; Seogsong Jeong; Jihun Song; Asaph Young Chun (BMJ Mental Health, 2025)
Background The association between the incidence of attention deficit hyperactivity disorder (ADHD) and the factors induced by the COVID-19 pandemic has not been fully investigated. Environmental stressors during or after the pandemic, including online classes and lifestyle disruptions, and postinfection neuroimmune changes likely contributed to the increase of ADHD.Methods The onset of ADHD was operationally defined as the diagnosis accompanied by a prescription history for ADHD medication. The incidence was observed among all Korean citizens (6–29 years). To evaluate the risk of ADHD, we established a retrospective and observational cohort, using data from the National Insurance Claims Database, the COVID-19 Vaccine Registry and the national surveillance system to find the patient. Our cohort (586 860 and 1 172 735 participants before and during the pandemic, respectively) comprised three age groups: school-aged children (6–12 years, n=227 276), adolescents (13–19 years, n=333 032) and young adults (20–29 years, n=1 199 287); sex ratio (male/female) was approximately 1.2.Results We analysed the incidence of ADHD in Korea (2012–2023), focusing on the COVID-19 pandemic’s impact on individuals. The incidence of ADHD increased during the pandemic, exceeding values predicted by negative binomial regression and autoregressive integrated moving average models. We also evaluated the risk of ADHD according to SARS-CoV-2 infection. As a result, these nationwide data revealed a significant rise in incidence (0.85 (before) vs 2.02 (during)), with SARS-CoV-2 infection identified as a critical risk factor.Conclusion These findings suggest the need for early intervention and neurological evaluations in ADHD risk groups, particularly among SARS-CoV-2-infected individuals.